Down Syndrome with Transient Myeloproliferative Disorder and Beta-Thalassemia Major - Garg, Amit (Springer India, 2014)
Down syndrome is the most common chromosomal abnormality and is frequently associated with transient myeloproliferative disorder (TMD) and leukaemias. The coinheritance of this syndrome with beta-thalassemia major is uncommon. Only two cases of coinheritance of Down syndrome with beta-thalassemia major have been published in literature. We report an infant suffering from Down syndrome who presented with severe anemia which was later attributed to beta-thalassemia major and TMD. The infant improved after blood transfusion and other supportive management. The blasts disappeared from marrow during hospital stay. In areas of high prevalence of beta-thalassemia heterozygotes, the presence of coinheritance of the mentioned condition with another congenital disorder may be common.